HADIS SEBAGAI SUMBER HUKUM ISLAM (Studi Metode Komparasi-Konfrontatif Hadis-Al- Qur’an Perspektif Muhammad Al-Ghazali dan Yusuf al-Qaradawi) - Amrulloh, A. (Ahkam: Jurnal Hukum Islam, 2015)
This article discusses the idea of Muhammad al-Ghazali (1917-1996 M) in his book, al-Sunnah al-Nabawiyyah bayna Ahl al-Hadith wa Ahl al-Fiqh, and Yusuf al-Qardawi, Kayfa Nata‘amalu ma‘a al-Sunnah al-Nabawiyyah, about comparative and confrontative method in determining the qualiy of the text of hadith. Regarding the position of al Quran and Hadith, both scholars employ the same method that is understanding hadith based on al quran. Yusuf Al Qardawi’ theory which is in line the criticism of conventional hadith is devoted to balance Muhammad al Ghazaly’ theory which is controversial in the decision of correct hadith. Identifying the similarity and differences between the two scholars is useful in deciding which hadith deserves to be used as source of law after al quran. Kata kunci: Sumber Hukum Islam, Kritik Hadis, Hadis-al-Quran, Muhammad al-Ghazali, Yusuf al-Qaradawi